2022
DOI: 10.1371/journal.pone.0275368
|View full text |Cite
|
Sign up to set email alerts
|

Four common vitamin D receptor polymorphisms and coronary artery disease susceptibility: A trial sequential analysis

Abstract: Background Studies on the susceptibility of vitamin D receptor (VDR) polymorphisms to coronary artery disease (CAD) reached controversial results. We performed this study for a more accurate evaluation between the VDR polymorphisms and CAD susceptibility. Methods PubMed, Embase, CNKI, Wan Fang, and VIP databases were searched. The odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to evaluate the associations. Trial sequential analysis (TSA) was introduced to estimate the positive association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…In addition, the TT genotype of rs2228570 exhibited an association with elevated levels of both LDL-c and HDL-c compared with the CC genotype. These results were consistent with previous studies that have also reported a notable correlation between the VDR (rs2228570) polymorphism and CAD risk in various populations, such as Chinese [46], Egyptian [47], and Iranian [48] populations. Moreover, a recent meta-analysis conducted by Tabaei et al [30] reinforced our results, demonstrating a significant association between the VDR (rs2228570) polymorphism and the risk of CAD.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the TT genotype of rs2228570 exhibited an association with elevated levels of both LDL-c and HDL-c compared with the CC genotype. These results were consistent with previous studies that have also reported a notable correlation between the VDR (rs2228570) polymorphism and CAD risk in various populations, such as Chinese [46], Egyptian [47], and Iranian [48] populations. Moreover, a recent meta-analysis conducted by Tabaei et al [30] reinforced our results, demonstrating a significant association between the VDR (rs2228570) polymorphism and the risk of CAD.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, this polymorphism may be predisposed to the development of premature CAD in healthy people with a family history of this disease over the next years [ 61 ]. According to the latest meta-analysis, the polymorphic variants rs2225870, rs1544410 and rs731236 are characterized by risk of CAD development, but the role of the rs7975232 polymorphism is ambiguous [ 62 , 63 ]. The role of genetic polymorphism in the VDR gene in CAD severity has been studied in only one article—the authors reported no associations between the rs1544410 and rs731236 polymorphisms with the severity of this disease [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Importantly, the genetic polymorphism of the vitamin D receptor may alter its role, and variations in ethnicity, lifestyle, and geographic conditions could potentially influence its effects. 8 The objective of this study was to assess the correlation between vitamin D levels and the findings of coronary artery computed tomography (CT) angiography in a Slovakian population.…”
Section: Introductionmentioning
confidence: 99%